"Don't sweat the small stuff": Understanding teacher resilience at the chalkface - Mansfield, Caroline; Beltman, Susan; Price, Anne; McConney, Andrew (Elsevier Science Ltd., 2012)
This study investigates how graduating and early career teachers perceive resilient teachers. Informed by survey data from 200 graduating and early career teachers, the study’s results indicate that graduating and early career teachers perceive that resilience for teachers comprises characteristics that are multi-dimensional and overlapping, and that views of resilience may develop according to teachers’ career stage. To further conceptualise teacher resilience, four possible dimensions of teacher resilience (profession-related, emotional, motivational and social) are suggested and the aspects within these dimensions are described. Some implications of this view of teacher resilience for preservice teacher education and future research are discussed.